All solid state battery
The three-layer electrode structure in all-solid-state batteries addresses resistance issues by using a porous base material with controlled pore diameter and solid electrolyte, enhancing ion conduction and reducing cracks.
Patent Information
- Application Number
- JP2022139180
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-09-01
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-09-01
AI Technical Summary
Existing all-solid-state batteries face issues with battery resistance due to volume changes in the electrode layer, leading to cracks and reduced ion conduction efficiency, which can be exacerbated by improper selection of porous base material and solid electrolyte properties.
The electrode layer is structured in a three-layer configuration, comprising a porous base material with a specific pore diameter and filled with solid electrolyte, along with active material, to mitigate volume changes and enhance ion conduction.
The three-layer structure reduces cracks, thereby lowering battery resistance and improving ion conduction efficiency, particularly effective for negative electrode layers.
Smart Images

Figure 0007619345000002 
Figure 0007619345000003 
Figure 0007619345000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to all-solid-state batteries. [Background technology]
[0002] Japanese Patent Application Laid-Open No. 2020-188026 (Patent Document 1) discloses a separator including a nonwoven fabric carrying a solid electrolyte. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-188026 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present disclosure aims to reduce battery resistance. [Means for solving the problem]
[0005] 1. In one aspect of the present disclosure, the all-solid-state battery includes an electrode layer. The electrode layer includes a first layer, a second layer, and a third layer. The second layer is interposed between the first layer and the third layer. The electrode layer includes a porous substrate, an active material, and a solid electrolyte. The porous substrate forms a skeleton of the second layer. The active material is included in each of the first layer and the third layer. The solid electrolyte is included in each of the first layer, the second layer, and the third layer. In the second layer, the solid electrolyte is filled in the porous substrate. The porous substrate has an average pore size of 21 μm or more. And the solid electrolyte has a D50 of less than 3 μm.
[0006] Hereinafter, "all-solid-state battery" may be abbreviated as "battery". Also, "solid electrolyte" may be abbreviated as "SE". For example, a sulfide solid electrolyte may be abbreviated as "sulfide SE".
[0007] Conventionally, an electrode layer is formed by coating an electrode slurry on a metal foil (current collector). The electrode layer contains an active material and an SE. The SE can form an ion conduction path in the electrode layer.
[0008] The electrode layer of the present disclosure has a novel structure. The electrode layer has a three-layer structure. The surface layers (first layer, third layer) contain an active material and an SE. The base layer (second layer) contains a porous substrate. The porous substrate forms the skeleton of the base layer. The porous substrate is filled with an SE.
[0009] In general, active materials may expand and contract with charging and discharging. The volume change of the active material causes a volume change of the electrode layer. The volume change of the electrode layer may cause cracks to occur in the electrode layer. The cracks in the electrode layer may reduce the efficiency of ion conduction. In the three-layer structure of the present disclosure, the porous substrate may mitigate the volume change of the electrode layer. Therefore, the occurrence of cracks may be reduced. The reduction of cracks is expected to reduce the battery resistance.
[0010] In order to further reduce cracks, it is also possible to configure the electrode layer only from the second layer. However, if the first and third layers are not present, a part of the porous substrate may be exposed on the surface of the electrode layer. The electrode layer contacts the separator layer, the current collector, etc. If a part of the porous substrate is exposed on the surface of the electrode layer, for example, the interface resistance between the separator layer (or the current collector) and the electrode layer may increase. As a result, the battery resistance may increase instead.
[0011] In addition, the average pore size of the porous substrate is 21 μm or more, and the D50 of the SE is less than 3 μm. If these conditions are not met, the battery resistance may increase. This is believed to be because the efficiency of ion conduction in the second layer decreases.
[0012] 2. In the all-solid-state battery described in "1" above, the active material may be, for example, a negative electrode active material.
[0013] That is, the electrode layer may be a negative electrode layer. The negative electrode active material tends to undergo a large volume change during charging and discharging. The three-layer structure of the present disclosure is considered to be particularly effective for the negative electrode layer.
[0014] 3. In the all-solid-state battery according to the above item "1" or "2," the porous substrate may be made of, for example, an insulating material.
[0015] According to the new findings of the present disclosure, when the porous substrate is made of a conductive material (e.g., metal, etc.), the carrier ions tend to become metal and precipitate. By making the porous substrate from an insulating material, the precipitation of metal can be reduced.
[0016] 4. In the all-solid-state battery according to any one of the above items "1" to "3", the active material may be contained in each of the first layer, the second layer, and the third layer. In the second layer, both the active material and the solid electrolyte may be filled in a porous substrate.
[0017] In addition to the SE, an active material may also be loaded into the porous substrate. Loading both the active material and the SE into the porous substrate may also reduce the battery resistance.
[0018] 5. In one aspect of the present disclosure, the all-solid-state battery includes a positive electrode layer, a separator layer, and a negative electrode layer. The separator layer is interposed between the positive electrode layer and the negative electrode layer. The negative electrode layer includes a first layer, a second layer, and a third layer. The second layer is interposed between the first layer and the third layer. At least one of the first layer and the third layer is in contact with the separator layer. The negative electrode layer includes a porous substrate, a negative electrode active material, and a solid electrolyte. The porous substrate forms a skeleton of the second layer. The porous substrate is formed of an insulating material. Both the negative electrode active material and the solid electrolyte are included in each of the first layer, the second layer, and the third layer. In the second layer, both the negative electrode active material and the solid electrolyte are filled in the porous substrate. The porous substrate has an average pore size of 21 to 97 μm. And the solid electrolyte has a D50 of 0.3 to 1.2 μm.
[0019] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the present embodiment do not limit the technical scope of the present disclosure. The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are non-restrictive. The technical scope of the present disclosure encompasses all modifications within the meaning and scope equivalent to the description of the claims. For example, it is originally intended that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined.
[0020] The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of..." are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a conceptual diagram of an all-solid-state battery according to this embodiment. [Diagram 2] FIG. 2 is a conceptual diagram of the electrode layer in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] <All-solid-state battery> FIG. 1 is a conceptual diagram of an all-solid-state battery in this embodiment. FIG. 1 conceptually shows a cross section parallel to the thickness direction of a battery 100. The battery 100 includes a power generating element 50. The battery 100 may include, for example, an exterior body (not shown). The exterior body may house the power generating element 50. The exterior body may be, for example, a pouch made of a metal foil laminate film, or a metal case. The battery 100 may include a single power generating element 50 alone, or may include a plurality of power generating elements 50. The plurality of power generating elements 50 may form, for example, a series circuit or a parallel circuit.
[0023] The power generating element 50 includes a first electrode layer 10, a separator layer 30, and a second electrode layer 20. The power generating element 50 may include a plurality of the first electrode layers 10, the separator layers 30, and the second electrode layers 20. As an example, the power generating element 50 in FIG. 1 includes two each of the first electrode layers 10, the separator layers 30, and the second electrode layers 20. The separator layer 30 is interposed between the first electrode layer 10 and the second electrode layer 20. The separator layer 30 separates the first electrode layer 10 from the second electrode layer 20. The separator layer 30 may include, for example, a sulfide SE. The separator layer 30 may have a thickness of, for example, 1 to 100 μm.
[0024] The second electrode layer 20 has a polarity different from that of the first electrode layer 10. For example, when the first electrode layer 10 is a positive electrode layer, the second electrode layer 20 is a negative electrode layer. The power generating element 50 may further include a first current collector 11 and a second current collector 21. The first current collector 11 is in contact with the first electrode layer 10. The second current collector 21 is in contact with the second electrode layer 20. For example, when the first electrode layer 10 is a positive electrode layer, the first current collector 11 is a positive electrode current collector. For example, when the second electrode layer 20 is a negative electrode layer, the second current collector 21 is a negative electrode current collector. The first current collector 11 and the second current collector 21 may each independently have a thickness of, for example, 5 to 50 μm. The first current collector 11 and the second current collector 21 may each independently include, for example, an Al foil, an Al alloy foil, a Cu foil, a Ni foil, a stainless steel foil, or the like.
[0025] 《Electrode layer》 The first electrode layer 10 and the second electrode layer 20 are collectively referred to as "electrode layers." At least one of the first electrode layer 10 and the second electrode layer 20 has a three-layer structure. The electrode layer may be a free-standing layer. A "free-standing layer" refers to a layer that maintains its shape by itself. Conventionally, an electrode layer has a single-layer structure and is a non-free-standing layer. A "non-free-standing layer" refers to a layer that is supported by a support (e.g., a current collector, etc.) and cannot maintain its shape by itself.
[0026] Fig. 2 is a conceptual diagram of the electrode layer in this embodiment. Fig. 2 conceptually shows a cross section parallel to the thickness direction of the electrode layer. The electrode layer includes a first layer 1, a second layer 2, and a third layer 3. The second layer 2 is interposed between the first layer 1 and the third layer 3.
[0027] The electrode layer may have a thickness of, for example, 1 to 1000 μm, 5 to 500 μm, or 10 to 100 μm. The first layer 1 has a first thickness T1. The second layer 2 has a second thickness T2. The third layer 3 has a third thickness T3. For example, the relationship of the following formula (1) may be satisfied.
[0028] 0.1≦T2 / (T1+T2+T3)≦0.9 …(1)
[0029] "T2 / (T1+T2+T3)" may be, for example, 0.2 to 0.8, 0.3 to 0.7, or 0.4 to 0.6. For example, the relationship "T1=T3" or "T1≠T3" may be satisfied. For example, the relationship "T2≧T1", "T2≧T3", etc. may be satisfied.
[0030] 《Second layer》 The second layer 2 is a base layer of the electrode layer. The second layer 2 includes a porous substrate and an SE. The porous substrate forms the skeleton of the second layer 2. The thickness of the porous substrate is equal to the second thickness T2. The SE is filled in the porous substrate. That is, the SE fills at least a part of the voids in the porous substrate. The second layer 2 may further include an active material, a conductive material, a binder, etc. In addition to the SE, the active material, the conductive material, and the binder may also be filled in the porous substrate.
[0031] The porous substrate may be, for example, in the form of a sheet. The porous substrate may have any structure. The porous substrate may include, for example, a nonwoven fabric, a foam, a three-dimensional mesh structure, etc. The porous substrate may be formed of, for example, a conductive material, a semiconductor material, or an insulating material. The porous substrate may include, for example, at least one material selected from the group consisting of metals, resins, and ceramics. The "conductive material" refers to a material having a molecular weight of 1×10 -3 Semiconductor materials have a volume resistivity of 1×10 -3 ~1×10 5 The volume resistivity of an insulating material is 1×10 5 The insulating material has a volume resistivity of 1×10 10 Ω cm or more, or 1×10 15 It may have a volume resistivity of Ω·cm or more.
[0032] The porous substrate may contain, for example, a thermoplastic resin. When the porous substrate contains a thermoplastic resin, for example, when the battery heats up, the porous substrate melts, and it is expected that the battery resistance increases and a sudden temperature rise is alleviated. The porous substrate may contain, for example, at least one selected from the group consisting of polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), and polyethylene terephthalate (PET). The porous substrate may have a melting point of, for example, 90 to 180°C, 100 to 150°C, or 110 to 130°C. The "melting point" refers to the peak top temperature of the melting peak (endothermic peak) in a DSC (Differential Scanning Calorimetry) curve. The DSC curve can be measured in accordance with "JIS K 7121".
[0033] The porous substrate has an average pore diameter of 21 μm or more. If the average pore diameter is less than 21 μm, the battery resistance may increase. The porous substrate may have an average pore diameter of, for example, 21 to 97 μm. The average pore diameter may be, for example, 21 to 57 μm, or 57 to 97 μm. The "average pore diameter" is measured by the following procedure. The surface of the porous substrate is imaged with a SEM (Scanning Electron Microscope) to obtain an SEM image. The SEM image is analyzed by image processing software "ImageJ". The maximum Feret diameter is measured for 50 pores (openings) randomly extracted from the SEM image. The arithmetic mean of the 50 maximum Feret diameters is regarded as the average pore diameter.
[0034] The porous substrate may have a porosity of, for example, 50% or more. The porous substrate may have a porosity of, for example, 50 to 89%. The porous substrate may have a porosity of, for example, 50 to 67% or 67 to 89%. The "porosity" is measured by the following procedure. A square sample is cut out from the porous substrate. The sample has a planar size of 50 mm x 50 mm. The mass and thickness of the sample are measured. The porosity is calculated by the following formula (2).
[0035] P = (1 - ρ / ρ0) × 100 … (2) P: Porosity [%] ρ: Apparent density (density calculated from the mass, thickness, and area of the sample) ρ0: True density (density of the constituent material of the porous substrate)
[0036] 《1st layer, 3rd layer》 The first layer 1 and the third layer 3 are surface layers of the electrode layer. The first layer 1 and the third layer 3 each cover the surface of the second layer 2. At least one of the first layer 1 and the third layer 3 is in contact with the separator layer. For example, the first layer 1 or the third layer 3 may be in contact with the separator layer. For example, the first layer 1 or the third layer 3 may be in contact with the current collector. The first layer 1 and the third layer 3 each independently contain an active material and an SE. The first layer 1 and the third layer 3 each independently may further contain a conductive material, a binder, etc.
[0037] 《Solid electrolyte》 The SE can form an ion conduction path in the electrode layer. The amount of the SE may be, for example, 1 to 30 parts by mass with respect to 100 parts by mass of the active material. The SE is particulate. The SE has a D50 of less than 3 μm. If the SE has a D50 of 3 μm or more, the battery resistance may increase. This is believed to be because the filling property into the porous substrate decreases. The SE may have a D50 of, for example, 2.5 μm or less, 2 μm or less, 1.2 μm or less, or 0.7 μm or less. The SE may have a D50 of, for example, 0.1 μm or more, 0.3 μm or more, or 0.5 μm or more. The SE may have a D50 of, for example, 0.3 to 1.2 μm. "D50" refers to the particle size at which the cumulative frequency from the smaller particle size reaches 50% in the volume-based particle size distribution. D50 can be measured by a laser diffraction particle size distribution measuring device.
[0038] For example, SE is 5m. 2 The specific surface area may be, for example, 10 to 21 m 2 / g, 10-18m 2 / g, or 18-21m 2The specific surface area may be 100 / g. The "specific surface area" is measured by the following procedure: 3 g of a measurement sample (powder) is placed in a measurement test tube. The measurement test tube is set in a specific surface area measurement device. A nitrogen gas adsorption test is performed in the specific surface area measurement device to obtain an adsorption isotherm. In the nitrogen gas adsorption test, the adsorption temperature is 77K, and the upper limit of the adsorption relative pressure is 0.99 (P / P0). The linear region of the adsorption isotherm is analyzed by the BET single point method to determine the specific surface area. The adsorption isotherm may be analyzed by analysis software.
[0039] The electrode layer may include at least one selected from the group consisting of, for example, sulfide SE, oxide SE, and fluoride SE. The sulfide SE may exhibit high ionic conductivity. The sulfide SE may include, for example, Li, P, and S. The sulfide SE may further include, for example, O, Ge, Si, etc. The sulfide SE may further include, for example, halogen, etc. The sulfide SE may further include, for example, I, Br, etc. The sulfide SE may be, for example, a glass ceramic type or an argyrodite type. Sulfides SE include, for example, LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-GeS2-P2S5, Li2S-P2S5, Li4P2S6, Li7P3S 11 and Li3PS4.
[0040] For example, "LiI-LiBr-Li3PS4" refers to a sulfide SE produced by mixing LiI, LiBr, and Li3PS4 in any molar ratio (ratio of amounts of substances). The sulfide SE may be synthesized by any method. The sulfide SE may be synthesized, for example, by a gas phase method, a solid phase method, or a liquid phase method. "Li2S-P2S5" includes Li3PS4. Li3PS4 may be produced, for example, by mixing Li2S and P2S5 in "Li2S / P2S5=75 / 25 (molar ratio)".
[0041] "Active Material" The active material causes an electrode reaction. The active material may be, for example, particulate. The active material may have, for example, a D50 of 0.1 to 30 μm. The active material may have, for example, a D50 of less than 3 μm. By having a D50 of less than 3 μm for the active material, it is expected that the filling property of the active material into the porous member is improved. The active material may have, for example, a D50 of 2.5 μm or less, 2 μm or less, 1.2 μm or less, or 0.8 μm or less. The SE may have, for example, a D50 of 0.1 μm or more, 0.3 μm or more, or 0.5 μm or more. The active material may have, for example, a D50 of 0.5 to 1.2 μm.
[0042] The active material may have, for example, a specific surface area of more than 3 m 2 / g. The active material may have, for example, a specific surface area of 8 to 14 m 2 / g, 8 to 12 m 2 / g, or 12 to 14 m 2 / g.
[0043] The active material may be, for example, a negative electrode active material. The negative electrode active material may contain, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, hard carbon, Si, SiO x (0 < x < 2), Si-based alloys, Sn, SnO x (0 < x < 2), Li, Li-based alloys, and Li4Ti5O 12 .
[0044] The active material may be, for example, a positive electrode active material. The positive electrode active material may contain, for example, at least one selected from the group consisting of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, Li(NiCoMnAl)O2, and LiFePO4. For example, in "Li(NiCoMn)O2", "(NiCoMn)" indicates that the total of the composition ratios in the parentheses is 1.
[0045] Other Ingredients The electrode layer may contain, for example, a conductive material. The conductive material can form an electron conduction path in the electrode layer. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the active material. The conductive material may contain, for example, at least one selected from the group consisting of acetylene black (AB), vapor grown carbon fiber (VGCF), carbon nanotube (CNT), and graphene flake (GF).
[0046] The electrode layer may contain, for example, a binder. The binder can bind solid materials together. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the active material. The binder may contain, for example, at least one selected from the group consisting of styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), and vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP).
[0047] The electrode layer may contain, for example, 0 to 10 parts by mass of a conductive material, 0.1 to 10 parts by mass of a binder, 1 to 30 parts by mass of SE, and the remainder being an active material. EXAMPLES
[0048] <No.1> 《Synthesis of sulfide SE》 Li2S and P2S5 were weighed to prepare a raw material powder. The mixture ratio of Li2S and P2S5 in the raw material powder was "Li2S / P2S5=75 / 25 (molar ratio)". The raw material powder and tetrahydrofuran (THF) were put into a glass container. The mixture ratio of the raw material and THF was "raw material powder / THF=1 / 20 (mass ratio)". The raw material powder and THF were stirred at 25°C for 72 hours. After stirring, a precipitate (powder) was collected. The precipitate is a precursor of sulfide SE. The precursor was dried at 25°C under an argon atmosphere to form a dried product. The dried product was fired at 100°C for 1 hour under atmospheric pressure (open system) to form a first fired product. The first fired product was vacuum sealed in a quartz tube. The quartz tube was fired in a muffle furnace at 140°C for 12 hours to form a second fired product. The second fired product was crushed to adjust the particle size. After crushing, the second fired product was fired at 200°C for 1 hour or more to obtain a sulfide SE. Hereinafter, the sulfide SE is also referred to as "LPS".
[0049] <<Formation of negative electrode layer>> As a kneading device, "Filmix (registered trademark)" manufactured by Hosokawa Micron Corporation was prepared. In the Filmix, 18.6 parts by mass of the negative electrode active material (Si), 8.69 parts by mass of the sulfide SE (LPS), 2.4 parts by mass of the conductive material (VGCF), a binder dispersion (SBR dispersion, concentration 5%), and a dispersion medium (diisobutyl ketone) were mixed to form a negative electrode slurry. The solid content rate of the negative electrode slurry was 43% (mass fraction). During kneading, the peripheral speed of the Filmix was adjusted within the range of 5 to 30 m / s. The negative electrode slurry was applied to both sides of a porous substrate (nonwoven fabric, thickness 10 μm) by a blade-type applicator, thereby forming a negative electrode layer. The nonwoven fabric was formed of PET fiber. The negative electrode layer was dried at 100° C. for 30 minutes. The negative electrode layer (self-supporting layer) includes a first layer, a second layer, and a third layer. The negative electrode layer had a thickness of 15 μm overall. The first layer and the third layer each include a negative electrode active material, an SE, a conductive material, and a binder. The second layer includes a porous substrate, a negative electrode active material, an SE, a conductive material, and a binder. In the second layer, the porous substrate is filled with the negative electrode active material, the SE, the conductive material, and the binder.
[0050] <<Formation of Separator Layer>> A separator slurry was formed by mixing 50 parts by mass of sulfide SE (LPS), a binder dispersion (SBR dispersion, concentration 5%), and a dispersion medium (diisobutyl ketone). The solid content of the separator slurry was 49% (mass fraction). The separator slurry was applied to the surface of the substrate to form a separator layer.
[0051] Formation of the positive electrode layer In a FILMICS mixing container, 80 parts by mass of positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2), 9.51 parts by mass of sulfide SE (LPS), and 2 parts by mass of conductive material (VGCF) were added. Then, binder dispersion (SBR dispersion, concentration 5%) and 32.21 parts by mass of dispersion medium (tetralin) were added to the mixing vessel. The solid content was 69% (mass fraction). The mixture was kneaded to form a positive electrode slurry. During kneading, the peripheral speed of the Filmix was adjusted within the range of 5 to 30 m / s. The positive electrode slurry was applied to one side of a positive electrode current collector (Al foil) using a blade-type applicator to form a positive electrode layer. The positive electrode layer was dried at 100°C for 30 minutes.
[0052] "assembly" A negative electrode layer was pressed onto both sides of a negative electrode current collector (Ni foil) by pressing at 20 kN. Next, a separator layer was pressed onto the negative electrode layer by pressing at 20 kN. Furthermore, a positive electrode layer was pressed onto the separator layer by pressing at 20 kN. This formed a power generating element. The power generating element was densified by applying roll pressing to the power generating element. The roll linear pressure was 4 ton / cm, and the roll gap was 100 μm. A positive electrode current collector (Al foil) was bonded to the positive electrode layer. A pouch made of Al laminate film was prepared as an exterior body. The power generating element was enclosed in the exterior body. A restraining member was attached to the outside of the exterior body so that a pressure of 5 MPa was applied to the power generating element. A test battery was manufactured as described above.
[0053] <Initial charge / discharge> CCCV charging and discharging (upper limit charge voltage 4.55V, lower limit discharge voltage 2.5V) was performed. The design capacity of the cell was 0.3Ah. The hour rate during CC charging or CC discharging was 0.1C. At an hour rate of 1C, the design capacity is discharged in 1 hour.
[0054] <No.2~16> Test batteries were fabricated similarly to No. 1, except that the powder properties of the negative electrode active material and sulfide SE, and the pore characteristics of the porous substrate were varied (see Table 1 below).
[0055] <No.17> In No. 17, a single-layered negative electrode layer was formed. That is, the test battery was manufactured in the following procedure. The negative electrode slurry was applied to both sides of the negative electrode current collector (Ni foil) to form a negative electrode layer (non-self-supporting layer). Next, the separator layer was pressed onto the negative electrode layer by pressing at 20 kN. Furthermore, the positive electrode layer was pressed onto the separator layer by pressing at 20 kN. This formed a power generating element. The power generating element was densified by applying roll pressing to the power generating element. The roll linear pressure was 4 ton / cm, and the roll gap was 100 μm. The positive electrode current collector (Al foil) was bonded to the positive electrode layer. A pouch made of Al laminate film was prepared as the exterior body. The power generating element was enclosed in the exterior body. A restraining member was attached to the outside of the exterior body so that a pressure of 5 MPa was applied to the power generating element.
[0056] <Evaluation> The discharge resistance of the test battery was measured at a SOC (State Of Charge) of 20%.
[0057] [Table 1]
[0058] <Result> The negative electrode layers of the test batteries No. 1 to 12 have a three-layer structure. The negative electrode layer of the test battery No. 17 has a single-layer structure. The test batteries No. 1 to 12 have reduced battery resistance (discharge resistance) compared to the test battery No. 17.
[0059] The negative electrode layers of Nos. 13 to 15 also have a three-layer structure. However, the test batteries Nos. 13 to 15 have higher battery resistance than the test battery No. 17. In Nos. 13 to 15, the D50 of the sulfide SE is 3 μm or more. In Nos. 13 to 15, the packing rate of the second layer is reduced.
[0060] The negative electrode layer of No. 16 also has a three-layer structure. However, the battery resistance of the test battery of No. 16 is higher than that of the test battery of No. 17. In No. 16, the average pore size of the porous substrate is less than 21 μm. [Explanation of symbols]
[0061] 1 first layer, 2 second layer, 3 third layer, 10 first electrode layer, 11 first current collector, 20 second electrode layer, 21 second current collector, 30 separator layer, 50 power generating element, 100 all-solid-state battery, T1 first thickness, T2 second thickness, T3 third thickness.
Claims
1. An electrode layer is included. the electrode layer includes a first layer, a second layer, and a third layer; the second layer is interposed between the first layer and the third layer, The electrode layer includes a porous substrate, an active material, and a solid electrolyte, The porous substrate forms a skeleton of the second layer; the active material is contained in each of the first layer and the third layer, the solid electrolyte is included in each of the first layer, the second layer, and the third layer; In the second layer, the solid electrolyte is filled in the porous substrate, The porous substrate has an average pore size of 21 μm or more; and The solid electrolyte has a D50 of less than 3 μm. All-solid-state battery.
2. The active material is a negative electrode active material. The all-solid-state battery according to claim 1 .
3. The porous substrate is formed of an insulating material. The all-solid-state battery according to claim 1 .
4. the active material is contained in each of the first layer, the second layer, and the third layer; and In the second layer, both the active material and the solid electrolyte are filled in the porous substrate. The all-solid-state battery according to claim 1 .
5. a positive electrode layer, a separator layer, and a negative electrode layer; the separator layer is interposed between the positive electrode layer and the negative electrode layer, the negative electrode layer includes a first layer, a second layer, and a third layer, the second layer is interposed between the first layer and the third layer, At least one of the first layer and the third layer is in contact with the separator layer; The negative electrode layer includes a porous substrate, a negative electrode active material, and a sulfide solid electrolyte, The porous substrate forms a skeleton of the second layer; The porous substrate is formed of an insulating material, Both the negative electrode active material and the sulfide solid electrolyte are contained in each of the first layer, the second layer, and the third layer; In the second layer, both the negative electrode active material and the sulfide solid electrolyte are filled in the porous substrate, The porous substrate has an average pore size of 21 to 97 μm; and The sulfide solid electrolyte has a D50 of 0.3 to 1.2 μm; All-solid-state battery.
Citation Information
Patent Citations
Electrode, battery, and method for manufacturing electrode
JP2012049090A
Electric device electrode and electric device using the same
JP2013084422A
Solid electrolyte sheet and all-solid secondary battery
JP2016139482A
Separator and manufacturing method thereof
JP2020188026A